PENGEMBANGAN MODUL PEMOGRAMAN MESIN CNC DASAR UNTUK KELAS XI TEKNIK PEMESINAN DI SMK MUHAMMADIYAH 3 YOGYAKARTA: Pengembangan Modul Pemograman Mesin CNC Dasar untuk Kelas XI Teknik Pemesinan Di SMK Muhammadiyah 3 Yogyakarta - Wildan Putra Handika (JURNAL VOKASI DEWANTARA (JVD), 2022)
The purpose of this study is to determine: (1) the characteristics of the CNC lathe machining module and (2) to test the effectiveness of the CNC lathe machining module. This study used a research and development. Research respondents were material experts, media experts, and students. The data analysis technique used qualitative techniques and quantitative data. The results show that: (1) the steps for developing a CNC lathe module were definitions for the analysis of the needs of media. At the design stage, a module design had been produced which will then be consulted with the supervisor. At the development stage, validation tests had been carried out on expert lecturers and teachers. The results were: 1) Validation of material expert lecturers received input, namely adding literature and exercises to each material. (2) The feasibility of the CNC lathe module, according to the material expert's assessment on the content aspect, the average score is 3 in the score range between> 2.50 to 3.25 on the eligible criteria. Based on the results of the material expert's assessment on the aspect of language selection, it was obtained a mean score of 3 in the score range between> 2.50 to 3.25 on the feasible criteria. Based on the results of the media expert's assessment on the graphic aspect, the mean score was 3.87 in the score range between 3.39 <x ≤ 4.18 on the feasible criteria.